Recent progress of dopant-free organic hole-transporting materials in perovskite solar cells *Project supported by the Scientific Research Starting Foundation for Overseas Introduced Talents of College of Chemistry, Nankai University. (January 2017) - Dongxue, Liu; Liu, Yongsheng
Abstract: Organic–inorganic hybrid perovskite solar cells have undergone especially intense research and transformation over the past seven years due to their enormous progress in conversion efficiencies. In this perspective, we review the latest developments of conventional perovskite solar cells with a main focus on dopant-free organic hole transporting materials (HTMs). Regarding the rapid progress of perovskite solar cells, stability of devices using dopant-free HTMs are also discussed to help readers understand the challenges and opportunities in high performance and stable perovskite solar cells.